On the design of Subly: Instilling behavior change during web surfing through subliminal priming - Caraban, Ana; Karapanos, Evangelos; Teixeira, Vítor; Munson, Sean A.; Campos, Pedro F. (My University, 2017)
With 50% of people spending over 6 h per day surfing the web, web browsers offer a promising platform for the delivery of behavior change interventions. One technique might be subliminal priming of behavioral concepts (e.g., walking). This paper presents Subly, an open-source plugin for Google’s Chrome browser that primes behavioral concepts through slight emphasis on words and phrases as people browse the Internet. Such priming interventions might be employed across several domains, such as breaking sedentary activity, promoting safe use of the Internet among minors, promoting civil discourse and breaking undesirable online habits such excessive use of social media. We present two studies with Subly: one that identifies the threshold of subliminal perception and one that demonstrates the efficacy of Subly in a picture-selection task. We conclude with opportunities and ethical considerations arising from the future use of Subly to achieve behavior change.
Keywords: Behavior change; Nudging; Persuasive technology; Subliminal